Consensus of linear multi-agent systems with exogenous disturbance generated from heterogeneous exosystems. Issue 15 (18th November 2017) - Zhang, Xuxi; Liu, Xianping
ABSTRACT: This paper addresses the consensus tracking problem for multi-agent linear systems subject to exogenous disturbances generated from heterogeneous exosystems. For the case that the disturbances are generated from linear heterogeneous exosystems, a linear disturbance observer and distributed control law are proposed, and sufficient condition for consensus tracking is established by combining the input-to-state stability and Lyapunov analysis methods. For the case when the disturbances are generated from non-linear heterogeneous exosystems, a non-linear disturbance observer is presented to estimate such disturbance by using the dynamic gain technique; then, a distributed control law is designed, and sufficient condition is also presented for achieving consensus tracking. Two simulation examples are provided to demonstrate the effectiveness of the proposed consensus protocols.